Grammatical reformulation in the sequencing of a complex action: the re-issuing of advice in radio phone-ins - Saunders, Kristina Maren (Kansas State University, 2013)
This conversation analytic study aims to describe how advice is re-issued in German in an institutional setting. Schank (1979) has shown that conversation during German advice programs consists of five different phases, one of which is the advice-giving phase. For the current study, four conversations from a radio advice program were analyzed. The data show that the advice-giving phase identified by Schank is further characterized by three sub-phases: 1) issuing of initial advice, 2) negotiation of rejected advice through reformulations of the initial advice, and 3) offer to move to the closing phase, done via generalization of the previously-given advice. I focus on the delivery of the second phase, in which the advice, previously rejected by the recipient, is re-issued using a number of discourse strategies on the part of the advice giver. These strategies include a change in recipient, a shift in source of the advice, the selection or change in reference (i.e. du ‘you’ vs. ich ‘I’), a change in advised action, and a change in strength. In selecting one of these identified discourse strategies, the advice giver addresses the reason for the rejection of the advice on which the reformulation is based. Finally, in looking at the third phase, I explain the function of generalizations and their role in situating the interlocutors interactionally within the larger advice-giving phase, thus sequencing the complex action (Schank, 1981).
Keywords: Conversation analysis; Advice; Advice rejection; Reformulation; Radio talk show; Language, Linguistics (0290)